Intimate partner violence perpetration and mental health service use in England: analysis of nationally representative survey data - Vishal Bhavsar; Sally McManus; Katherine Saunders; Louise M. Howard (BJPsych Open, 2023)
Background Intimate partner violence perpetration (IPVP) is associated with psychiatric disorders, but an association with mental health service use has not been fully established and is relevant for policy. Mental health service contact by perpetrators of intimate partner violence presents an opportunity for reducing harmful behaviours.